2005
DOI: 10.1007/s00213-004-2091-4
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced dopamine release in the medial prefrontal cortex is augmented by a moderate concentration of locally administered tyrosine but attenuated by high tyrosine concentrations or by tyrosine depletion

Abstract: Basal extracellular levels of DA in the MPFC and striatum are not affected by wide changes in tyrosine availability. However, modestly increased brain tyrosine levels can augment CLZ-induced MPFC and HAL-induced DA levels. Very high tyrosine concentrations attenuate HAL-induced striatal DA levels. These data may explain inconsistencies in the literature and suggest that tyrosine availability could be exploited to modulate psychotropic drug-induced DA levels in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
1
9
1
Order By: Relevance
“…Other studies reported that acute treatment with SSRI-antipsychotic combination, including Hal-Flu, increased extracellular DA release in rat PFC (Ago et al 2005 ;Koch et al 2004 ;Zhang et al 2000). Clz has also been reported to increase DA release in PFC (Devoto et al 2003 ;Jaskiw et al 2005). Such apparent discrepancy with our findings can be explained by methodological differences between the studies.…”
Section: The Regulatory Effects Of Hal-flu On Cell-signaling Pathwayscontrasting
confidence: 82%
“…Other studies reported that acute treatment with SSRI-antipsychotic combination, including Hal-Flu, increased extracellular DA release in rat PFC (Ago et al 2005 ;Koch et al 2004 ;Zhang et al 2000). Clz has also been reported to increase DA release in PFC (Devoto et al 2003 ;Jaskiw et al 2005). Such apparent discrepancy with our findings can be explained by methodological differences between the studies.…”
Section: The Regulatory Effects Of Hal-flu On Cell-signaling Pathwayscontrasting
confidence: 82%
“…Groups of animals (n=6) were treated with vehicle (saline), LiCl 2 chloride (3 mg/kg IP) or selected combinations of these treatments and HAL (0.19 mg/kg SC)+TYR (100 mg/kg SC). For comparison, some groups also were treated with NAA(−), a mixture of neutral amino acids known to lower brain TYR levels (Jaskiw et al, 2005; McTavish et al, 1999). The treatment schedule was the same as that for evaluation of catalepsy.…”
Section: Resultsmentioning
confidence: 99%
“…In order for TYR administration to augment DA synthesis and/or efflux, the availability of TYR rather than activity of tyrosine hydroxylase must become rate limiting for DA synthesis; this normally requires activation of tyrosine hydroxylase as well and/or a lowering of tyrosine availability (Bongiovanni et al, 2005; Jaskiw and Bongiovanni, 2004; Jaskiw et al, 2001, 2005, 2008; Milner and Wurtman, 1986). HAL, for instance, potently activates tyrosine hydroxylase (Salvatore et al, 2000; Zivkovic and Guidotti, 1974) and modestly lowers TYR levels in striatal tissue (Bongiovanni et al, 2006; Westerink and Wirix, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…When TH is activated, however, tyrosine availability can affect DA synthesis (Carlsson and Lindqvist 1978;Sved and Fernstrom 1981;Westerink and Wirix 1983) as well as levels of DA and metabolites (Scally et al 1977;Sved and Fernstrom 1981;Fernstrom et al 1984Fernstrom et al , 1989Milner and Wurtman 1986;During et al 1989;DePietro and Fernstrom 1999;Jaskiw et al 2001Jaskiw et al , 2005. This phenomenon is particularly evident when TH activation is superimposed on limited tyrosine availability (McTavish et al 1999b;Jaskiw et al 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Tyrosine crosses the BBB by facilitated diffusion, via a carrier that it shares competitively with other large neutral amino acids (NAAs) (Pardridge and Oldendorf 1975;Pardridge 1977;Smith et al 1987;Verrey 2003). Systemic administration of a tyrosine-and phenylalanine-free mixture of large NAAs [NAA(−)] can reduce brain tyrosine levels both by increasing competition for BBB transport and by lowering plasma tyrosine levels through stimulation of peripheral protein synthesis (Biggio et al 1976;Fernstrom and Fernstrom 1995;McTavish et al 1999b;Jaskiw et al 2005). NAA(−) reduces basal striatal DA synthesis as well as amphetamine-or haloperidol-induced extracellular striatal DA levels (McTavish et al 1999b;.…”
Section: Introductionmentioning
confidence: 99%